Application of Marine Spatial Planning tools for tidal stream farm micro-siting. (1st April 2022) - Álvarez, M.; Ramos, V.; Carballo, R.; López, I.; Fouz, D.M.; Iglesias, G.
Abstract: The operation of tidal stream energy farms may interfere with other uses of the marine space, especially in depth-limited areas (estuaries, rivers, etc.) which are typically subject to multiple demands of use. The Marine Spatial Planning Directive (MSP) was passed by the European Commission in 2014 to ensure a harmonic coexistence between different maritime activities and to protect the marine environment. In this context, the objective of this work is to present a methodology based on MSP tools for tidal-farm siting in depth-limited areas. The methodology is illustrated through a case study: Ria de Ribadeo, a shallow-water estuary in NW Spain. Having considered a number of uses (archaeological, biodiversity, fishing, aquaculture, recreational and navigation), two exploitable tidal farm sites (Areas A and C) with annual energy densities of 1 GWhm − 2 were found. The estuary is periodically dredged to maintain navigation. Dredging-related risks were analysed using a novel indicator, the Dredging Associated Risk (DAR), based on which Area C was discarded and Area A had its exploitable surface area reduced by 25%. In sum, the methodology proposed was proven to be effective for tidal stream farm planning. Graphical abstract: Highlights: MSP streamlines licensing for tidal farms and arbitrates conflicts with other users. At depth-limited tidal sites, currents are highly sensitive to bathymetric changes. DAR is proposed to assess dredging-related risks at depth-limited tidal sites. MSP is a useful tool to find optimum locations for tidal farm operation.